O desejo não tem idade a sexualidade da mulher idosa - Ramos, Rute Bacelar de Araújo (2001)
The aim of this work is to investigate sexual behaviour aspects of the elderly woman. Using the qualitative method and discourse analysis, we heard married, single and widowed wornem with ages over 68. We found out that information about this issue is poor and surrounded by prejudice and that natural aspects about human life turn out to be full of complexities due to ignorance or absence of reliable information, turning sexuality into something apart from life. Several factors that substantiate such points of view in our cultura, are disseminated in the family and throughout society. From a scientific bearing, looking into the personage of this situation the elderly wornan , we sought na understanding of the reasons why sexuality is seen as it is, at this point in life. We then discovered that the most significant forces drawing its expressions, ]ay in culture itself and after that, the family and the social rules Despite that, her Desire does not cool off, so we reached the conclusion that it's necessary to create a new cultural profile. With the language, not only as a mean for oral communication, but also being a way to date the other party, we'll be able to reach the family, the education and the whole social environment, acting upon individual and colective subjectivity, redirecting perceptions, feelings and behaviour regarding such a meaningful theme